Catalytic Kinetic Spectrophotometric Method for the Determination of Traces of Iron - Zhai, Qing-Zhou; Guo, Hai-Qiang (Asian Journal of Chemistry, 2010)
A novel kinetic spectrophotometric method for the determination of trace iron is developed based on the catalytic effect of Fe(III) on the oxidation reaction of dibromo-p-chloro-chlorophosphonazo (DBC-CPA) by potassium periodate. In the medium of 1.0 × 10-2 mol/L of sulfuric acid, the maximum absorption peak of Fe(III)-(DBC-CPA)-KIO4 system locates at 548 nm. The absorbance difference (ΔA) is linearly related with the concentration of iron(III) over the range of 0.010-0.15 μg/mL and fitted the equation: ΔA = 5.810C (C: μg/mL) + 0.1592, with a regression coefficient of 0.9936 at the wavelength. The detection limit of the method is 5.06 ng/mL. The method was used to determine trace iron in the blood sample of human. The relative standard deviation was 0.87-1.42 % for 11 replicate determinations. The recovery of the standard addition was 99.98-100.7 %. The analytical results were in good agreement with those of atomic absorption spectrometry.